Perspectives from a National Reference Laboratory surveillance program on Aspergillus epidemiology and azole resistance” - painel “Fungal infections in Portugal”, - Sabino, Raquel (2021)
A retrospective laboratory-based study (2017-2018) on Aspergillus surveillance was performed at the national mycology reference laboratory of Portugal. The primary objective were the knowledge of the molecular epidemiology of clinical and environmental Aspergillus isolates. A. fumigatus sensu stricto was the most frequent species in both clinical and environmental sources. A very high frequency of cryptic species was identified. A second objective was the determination of the frequency of azole resistance of A. fumigatus. All isolates included in our collection (2012-2019) identified as belonging to Fumigati section were recovered and screened. The overall frequency of resistance to azoles in A. fumigatus sensu stricto was 3.0% (four clinical and five environmental isolates). The TR34/L98H mutation, linked to environmental transmission route of azole resistance the most frequently detected mutation, found in three environmental and one clinical isolate (1.4%).